Penerapan Media Edukasi Berbasis Gamifikasi dalam Upaya Pencegahan Stunting di Kabupaten Timor Tengah Selatan - Rr Eko Susetyarini; Beti Istanti Suwandayani; Baiduri Baiduri; Yus Mochamad Cholily; Arina Restian; Kuncahyono Kuncahyono; Roimil Latifah (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Stunting remains a public health issue in Indonesia, particularly in areas with limited access to information, such as South Central Timor (TTS) Regency, East Nusa Tenggara. Low nutritional literacy among elementary school teachers and (integrated health post) volunteers hinders stunting prevention efforts at the community level. This community service initiative aims to improve stunting literacy through gamification-based educational media as part of the GEMBIRA (Clean and Healthy Community Movement) program. The program was implemented in five stages: dissemination, training, technology application, mentoring and evaluation, and sustainability. The participants included 65 elementary school teachers (from the Teacher Working Group/KKG) and 15 volunteers. Pre-test and post-test evaluations demonstrated a significant increase in knowledge; scores for teachers rose from 52.4 to 94.8 (an 80.9% increase), while scores for volunteers rose from 48.0 to 85.5 (a 78.1% increase). The gamification approach proved effective in enhancing health literacy and holds potential as a sustainable model for stunting education.